Adubação da cultura da soja com dejetos de animais no Oeste do Paraná - Blanco, Idelvan Bonadiman (2015)
The increase in productivity of soy beans in recent years happened, basically, for the adoption of technologies such as the use of inputs and equipments, which are directly related to the cost of production. Among the inputs used, fertilizers are more expensive. The western Parana has a large number of pigs and poultry integrators, generating a lot of animal waste. The use of animal waste as fertilizer is a rational alternative of great interest in terms environmental, economic, social and agronomic. Thus the objective of this study was evaluate the effects of different doses application of poultry litter and pig slurry, in to the macronutrient content into soil and soy bean leaves as on grains and soy bean oil compared to mineral fertilization. The experimental area is located at the Experimental Station of the Agronomic Institute of Paraná, in Santa Tereza do Oeste - PR. The treatments were generated by factorial (2x3)+1+1, being two waste (liquid swine and poultry litter) with three doses of each (poultry litter: 1.2, 2.4 and 3.6 t / ha (wet basis) and pig slurry: 48, 96 and 144 m3 (cubic meter) / ha). Others additional treatments were the control (no fertilization) and mineral fertilization (300 kg/ha of the formulated 04-30-10). Experimental delineation adopted was random blocks with three repetitions. The animal manure fertilization resulted in higher levels of P and K into soil and greater absorption of N and P by plants, beyond a higher percentage of lodged plants in relation to the control and mineral fertilization. Grains productivity and soy bean oil income were similar between animal waste and mineral fertilization and higher than the control. It demonstrated both fertilizations are effective providing nutrients for the soy bean culture.